Effects of perforations on load carrying mechanism of perforated hollow sections inspired by nature / Woo Yian Peen and Syahrul Fithry Senin - Woo, Yian Peen; Senin, Syahrul Fithry (2012)
Sustainability in built environment has attracted more attention, effort to increase efficiency of materials and elements used in construction becomes more important. Structural members in construction should be made more efficient in terms of the ratio of load carrying capacity to self-weight without compromising the safety of the structure as a whole. In this respect, nature offers a lot of idea to be copied and explored. Inspired by the Cholla cactus skeleton, this study investigates how the load carrying capacity of hollow structural members affected by perforations. Computational analysis using finite element method has been carried out for a total 12 models with different perforation patterns in order to investigate the strength and stiffness of models under compressive, flexural and torsional load cases. The results of perforated hollow sections have been compared with the control model without perforation. It is found that load carrying capacity not only influenced by change in section properties, but also by the perforations arrangement patterns and the load path before and after the loads being interrupted by the perforations where the spiral arrangement pattern has significant influence in certain load cases. Findings from this study is essential in leading to proposal of efficient structural members.